Determination of complex permittivity of arbitrarily shaped homogenous materials via waveguide measurements - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2017)
In this study, complex permittivity of arbitrarily shaped homogenous materials loaded in different shaped waveguides (rectangular waveguide and circular waveguide) is determined through an iterative inverse algorithm. S-parameters are calculated for chosen material numerically via Method of Moments (MoM), in place of real measurement data for sake of testing algorithm as a first step. Inverse algorithm depends on calculating transmission-reflection coefficients (two port S-parameters) with respect to updated complex permittivity, started with an initial guess. At each step, calculated S-parameters (either S11 and/or S21) can be used to update complex permittivity in sense of Newton-Raphson numerical approach. Problem is reduced to finding the roots of iterative equation, which is a function of complex permittivity. © 2017 Euraap.
Keywords: circular waveguide; complex permittivity determination; MoM; rectangular waveguide